Induction of intercellular adhesion molecule 1 and class II histocompatibility antigens in colorectal tumour cells expressing activated ras oncogene. Issue 6 (December 1995) - Stoneman, V; Morris, A
Abstract : Aims —To determine whether there is a correlation between activation of the ras oncogene and the induction of MHC class II antigens and intercellular adhesion molecule 1 (ICAM-1) by interferon-γ (IFN-γ). Methods —Expression of class II antigens, ICAM-1 and intracellular ras oncoprotein (p21) in established colorectal cell lines and short term cultures of primary colorectal tumour cells was determined by flow cytometry and mutation in the ras gene by sequencing of amplified segments of the gene. Results —The cell lines showed a variation in their modulation of MHC class II antigens and ICAM-1, ranging from no induction to a 98-fold increase in class II antigen expression in the HT29 cell line. Previous work indicated that most tumours could not be induced to express class II antigens. Four of the five least inducible lines either contained mutant ras or highly expressed the oncoprotein. The four highly inducible cell lines all contained non-mutant ras . Of the 21 tumours studied in primary culture, 10 were inducible, one of which contained mutant ras . Of the remaining non-inducible tumours, four were mutant. Conclusions —Correlations between ras activation and failure to respond to IFN-γ could not be shown to be significant. Therefore, ras activation, and concomitant subversion of intracellular signalling pathways, is probably not the major determinant in failure to activate class II antigens and ICAM-1.